Identification of lactic acid bacteria in the feces of dairy cows fed whole crop maize silage to assess the survival of silage bacteria in the gut. (8th September 2017) - Han, Hongyan; Wang, Chao; Li, Yanbing; Yu, Zhu; Xu, Qingfang; Li, Guangpeng; Minh, Tang Thuy; Nishino, Naoki
Abstract: In order to assess the survival of lactic acid bacteria (LAB) in whole crop maize silage in the gut of dairy cows, one representative silage sample and three different feces samples were collected from dairy cows on three dairy farms in Hua Bei, China and three dairy farms in Kyushu, Japan. The composition of the bacterial community was examined by denaturing gradient gel electrophoresis and quantitative polymerase chain reaction. Lactobacillus acetotolerans was detected in all bunker‐made maize silage samples, regardless of the dairy farm or sampling region from which they were sourced. A total of eight LAB species were detected in the maize silage samples, of which three ( L. acetotolerans, L. pontis and L. casei ) appeared to survive digestion. The populations of L. acetotolerans in silage and feces were 10 6–7 and 10 3–4 copies/g, respectively, indicating that, even for the LAB species showing potential survival in the gut, competition in this niche may be harsh and the population may substantially decrease during the digestion process. It may be difficult for silage LAB to survive in the gut of silage‐fed dairy cows, because marked decrease in population can take place during the digestion process, even for surviving species.